Integrating Building Information Modelling (BIM) and Sustainability to Greening Existing Building: Potentials in Malaysian Construction Industry - Zulkefli, Nur Syamimi; Mohd-Rahim, Faizul Azli; Zainon, Nurshuhada (International Journal of Sustainable Construction Engineering and Technology, 2020)
Apropos to numerous environmental issues highlighted globally and locally, Malaysia has now moving forward towards new agenda of greening the cities. A positive movement trend of new green building in the country can be seen as number of projects going into green rating application are increasing yearly. Nevertheless, sustainability impact is considered as significantly small since newly developed green building represent small percentage as compared to the existing non-green building. Therefore, the idea of greening the existing building through refurbishment emerged in order to achieve wider sustainability objectives. Apart from that, supported with recent evolvement of technology and digitalization in construction industry, in lieu with governments’ strategies to adopt Industry 4.0, Building Information Modelling (BIM) has also been acknowledged and used broadly as a solution to integrate and facilitate management of information throughout building lifecycles. Considering these two areas; sustainability and BIM are continuously gaining momentum these days, this paper attempts to explore BIM’s potentials as an enabler to help greening the existing non-green building. Literature review is conducted focus on reviewing BIM and sustainability present status in Malaysian construction industry, also their relationship including examining potential areas where BIM may contribute to enhance the buildings’ sustainability performances. Based on the reviews, there is a potential of bridging the two areas considering both has becoming a national construction industry agenda since the government released CITP2016-2020. To further concur the ideas, literature reviews has also proven that the ability of BIM to facilitate various functions has enable it to support several sustainability analyses such as energy, carbon emission, lighting, water, materials and waste, building and site, and costing analysis.